2014
DOI: 10.1254/jphs.14046fp
|View full text |Cite
|
Sign up to set email alerts
|

Soluble Guanylate Cyclase Redox State Under Hypoxia or Hypoxia/Reoxygenation in Isolated Monkey Coronary Arteries

Abstract: Abstract. Hypoxia or hypoxia/reoxygenation impairs nitric oxide (NO)-mediated relaxation through the increase in superoxide generation in monkey coronary arteries. Soluble guanylate cyclase (sGC), the target enzyme of NO, has been shown to change from the NO-sensitive reduced form to the NO-insensitive oxidized/heme-free form under substantial oxidative stress, so the present study investigated whether hypoxia or hypoxia/reoxygenation influences sGC redox equilibrium. In isolated monkey coronary arteries witho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 29 publications
1
19
0
Order By: Relevance
“…In the previous study, we have shown that superoxide, a precursor of peroxynitrite, has an ability to shift the sGC redox equilibrium toward the NO-insensitive form in isolated endothelium-denuded monkey coronary [22] and rat iliac arteries [21]. Based on this observation, we next examined whether superoxide contributes to the effects of peroxynitrite on the relaxant responses to BAY compounds.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the previous study, we have shown that superoxide, a precursor of peroxynitrite, has an ability to shift the sGC redox equilibrium toward the NO-insensitive form in isolated endothelium-denuded monkey coronary [22] and rat iliac arteries [21]. Based on this observation, we next examined whether superoxide contributes to the effects of peroxynitrite on the relaxant responses to BAY compounds.…”
Section: Discussionmentioning
confidence: 99%
“…The content of cGMP in endothelium-denuded rat iliac artery strips was measured according to the method described previously with minor modifications [22]. Briefly, the strips were incubated without (referred to as ‘basal') and with BAY 41-2272 (10 -7 M ) or BAY 60-2770 (10 -9 M ) for about 20 min after exposing to each condition and were then immediately plunged into liquid nitrogen.…”
Section: Methodsmentioning
confidence: 99%
“…Briefly, increased intracellular superoxide scavenges nitroglycerin-derived NO within the smooth muscle [10] and oxidizes sGC heme to the NO-insensitive state [18], both of which result in a decrease in NO bioavailability in the coronary artery. On the other hand, Zheng et al [9] demonstrated that hypoxia increases sGC dimerization probably through superoxide overproduction in porcine coronary arteries.…”
Section: Discussionmentioning
confidence: 99%
“…The efficacy of this type of drug has been suggested to be enhanced under oxidative stress, which is causally involved in many cardiovascular diseases (Stasch et al 2006), so its clinical application is highly desirable. In this regard, basic research has shown the utility of sGC activators in the therapy for coronary artery disease (Bice et al 2014;Tawa et al 2014) and heart failure (Boerrigter et al 2007;Fraccarollo et al 2014). Therefore, it may be possible to use sGC activators as substitute drugs for organic nitrates.…”
Section: Introductionmentioning
confidence: 99%